Use of Ulva reticulata as a growth supplement for tomato (Solanum lycopersicum) - Abu, Nor Jawahir; Bujang, Japar Sidik; Zakaria, Muta Harah; Zulkifly, Shahrizim (Public Library of Science, 2022)
Mass proliferation and accumulation of the green macroalga Ulva reticulata are problems in coastal areas and affect other ecosystems, such as those involving seagrasses. In the absence of any intervention, the decomposition of these macroalgae over time can disrupt the balance of recipient ecosystems. Attention has been given to the potential use of U. reticulata as a supplier of nutrients for crop species such as tomatoes as a possible solution to the buildup of this unusable seaweed species, which is usually left to decompose in affected seagrass ecosystems; this is the case in the Merambong seagrass meadow in the Sungai Pulai estuary in Gelang Patah, southwestern Johor, Malaysia. We analyzed the macro- and micronutrient contents in U. reticulata to determine nutrient availability. We also performed greenhouse studies to test the effects of crude extracts from dried U. reticulata-Extract “A” and fresh U. reticulata-Extract “B” on plant growth, total yield, and quality vine-ripened fruits. Compared to other seaweed extracts used as plant growth promoters, U. reticulata extracts have higher nitrogen (N), manganese (Mn), zinc (Zn), and iron (Fe) contents. The application of 30% Extracts “A” and “B” and 50% Extracts “A” and “B” significantly affected tomato plant height. However, extract concentrations that promoted plant height and hastened flowering and fruiting did not increase total fruit yields. Both treatments that positively affected tomato plant height and hastened flowering and fruiting resulted in increased contents of total soluble solids (TSS), beta-carotene, lycopene, ascorbic acid and total titratable acidity (TTA) in the vine-ripened fruits. Agronomically, the application of 5% Extracts “A” and “B”, 10%-20% Extracts “A” and “B”, and 50% Extract “A” doubled the total yield compared to those of the control, and 40% Extract “A” resulted in the highest total fruit yield. In general, tomato plants responded well to Extract “A” than Extract “B” and presented good total fruit yield and quality.